Advancing human disease research with fish evolutionary mutant models. Issue 1 (January 2022) - Beck, Emily A.; Healey, Hope M.; Small, Clayton M.; Currey, Mark C.; Desvignes, Thomas; Cresko, William A.; Postlethwait, John H.
Abstract : Model organism research is essential to understand disease mechanisms. However, laboratory-induced genetic models can lack genetic variation and often fail to mimic the spectrum of disease severity. Evolutionary mutant models (EMMs) are species with evolved phenotypes that mimic human disease. EMMs complement traditional laboratory models by providing unique avenues to study gene-by-environment interactions, modular mutations in noncoding regions, and their evolved compensations. EMMs have improved our understanding of complex diseases, including cancer, diabetes, and aging, and illuminated mechanisms in many organs. Rapid advancements of sequencing and genome-editing technologies have catapulted the utility of EMMs, particularly in fish. Fish are the most diverse group of vertebrates, exhibiting a kaleidoscope of specialized phenotypes, many that would be pathogenic in humans but are adaptive in the species' specialized habitat. Importantly, evolved compensations can suggest avenues for novel disease therapies. This review summarizes current research using fish EMMs to advance our understanding of human disease. Highlights: Some animals evolved natural phenotypes that mimic human diseases but are not pathogenic in the animals' specific environments. Understanding molecular genetic strategies that evolutionary mutant medical models use to compensate for their pathology-mimicking phenotypes can suggest new avenues for novel therapies. Understanding evolutionary mutant models illuminates the role of genetic variation in disease etiology. Technical advances in genomics and molecular biology facilitate the expansion of disease research to non-model organisms. The deep radiation of fish generated a kaleidoscope of specialized phenotypes that mechanistically mimic human disease. Here we describe seven fish EMMs used to tackle research on nine groups of human diseases.